Modeling photovoltaics' waste projection and waste management optimization. (15th February 2023) - Rabaia, Malek Kamal Hussien; Semeraro, Concetta; Olabi, Abdul-Ghani
Abstract: The world is moving towards renewable energies as an alternative to fossil fuels. The photovoltaic technologies have the highest capacity increase rate among all the renewable energy systems throughout the last decade. Therefore, the huge amounts of photovoltaic wastes from such significant global installations are inevitable and needs to be dealt with sooner than later to increase the potential of PVs being an affordable and clean energy source. This work is split into two parts with different models. The first one mathematically models the PV waste projection using the Weibull distribution and socio-environmental decision-making factors while connecting them to the power purchase agreements (PPAs). This model uses data from both c-Si and CdTe PV projects in the United Arab Emirates (UAE). This model's results showed the possibility of increasing the PV projects operational age in UAE to 30 years for both technologies with 2030 being the best and latest year to start PV waste management procedures with the profitable reusability of PVs after projects' decommissioning. The second part is an optimization model for the PV waste and installations management by controlling the total future PV installations and possible PV replacements, while considering budget limitations and dismantling capacities. With a planning horizon until the year of 2100, this model's results suggest annually installing 670 MW of new PVs to achieve 50% of the country's consumption by 2030 and 100% by 2040 without any power shortage or outage. Finally, the models are flexible and extremely beneficial for future works for improvements, results comparison, and to design PV waste management centers or dismantling facilities. Highlights: Projected PV wastes through socio-environmental factors and Weibull distribution. Built an optimization model to balance PV installations with waste replacements. Unprecedently improved both c-Si and CdTe PV waste management plans in the UAE. Install 670 MW of PVs annually to achieve 50% of the country's consumption by 2030. Required annual replacements will start exceeding 100 MW by 2040.